2016
DOI: 10.1016/j.bbi.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Repeating patterns of sleep restriction and recovery: Do we get used to it?

Abstract: Despite its prevalence in modern society, little is known about the long-term impact of restricting sleep during the week and ‘catching up’ on weekends. This common sleep pattern was experimentally modeled with three weeks of 5 nights of sleep restricted to 4 hours followed by two nights of 8-hour recovery sleep. In an intra-individual design, 14 healthy adults completed both the sleep deprivation and an 8-hour control condition, and the subjective impact and the effects on physiological markers of stress (cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 42 publications
3
45
0
Order By: Relevance
“…The effectiveness of scheduled weekend recovery sleep (i.e., experimentally controlled recovery sleep opportunities) as a strategy to mitigate adverse physiological consequences of insufficient sleep has been examined for whole-body insulin sensitivity, inflammatory proteins, and blood pressure [26][27][28][29][30]. Findings from these studies are mixed with evidence for and against improved physiological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of scheduled weekend recovery sleep (i.e., experimentally controlled recovery sleep opportunities) as a strategy to mitigate adverse physiological consequences of insufficient sleep has been examined for whole-body insulin sensitivity, inflammatory proteins, and blood pressure [26][27][28][29][30]. Findings from these studies are mixed with evidence for and against improved physiological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study to-date has investigated the physiological effects of repeated cycles of sleep restriction and recovery in healthy adults. 15 It found that stress responses were continually elevated throughout the sleep restriction cycles. It is still unclear how sleep architecture responds to repeated cycles of sleep restriction in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The full list of inclusion and exclusion criteria are presented in Simpson et al . (). This study was approved by the Institutional Review Board for the Protection of Human Subjects at Beth Israel Deaconess Medical Center.…”
Section: Methodsmentioning
confidence: 97%
“…The study paradigm is described in detail in Simpson et al . (). During the rested sleep control condition, participants were provided with 8 h of enforced sleep opportunity per night (23:00–07:00 hours) for 3 weeks.…”
Section: Methodsmentioning
confidence: 97%